An Efficient and Eco-Friendly Lake Bin Machine - Muhammad Nazirul Aiman Mahadi; Misman, Dalila; Muhammad Rusydi Muhammad Razif (Progress in Engineering Application and Technology, 2022)
Water pollution occurs when pollutants are released into water, making it unsuitable for human consumption and disrupting aquatic ecosystems. Many wastewater collectors have previously been developed by scientists and innovators worldwide, with the primary goal of cleaning up our rivers with minimal human participation. This study offers a prototype of a more environmentally friendly water garbage collector than previous garbage collectors for collecting garbage on the water surface. The prototype has also been tested and inspected in terms of body buoyancy, battery power charge rate using solar energy, the weight of waste that can be accommodated and collected by the machine, and suction power of the water pump used. The goal is to clean up small lakes, rivers and narrow drains in Malaysia. It can operate at a distance of 4 meters and collect 1 kilogram in 1 hour, according to test findings in lakes and rivers.